Detecting drought-induced GPP spatiotemporal variabilities with sun-induced chlorophyll fluorescence during the 2009/2010 droughts in China - Shiliu Chen; Yuefei Huang; Guangqian Wang (Ecological Indicators, 2021)
In the parallel with the climate change, droughts have become one of the major climate extremes that induce losses in the terrestrial gross primary production (GPP). However, studying of the drought effects on GPP is still challenging, partly due to the lack of direct observations of GPP at large scales. Aiming to explore the potential of spaceborne sun-induced chlorophyll fluorescence (SIF) in monitoring vegetation droughts and quantifying the drought-induced GPP variabilities, we evaluated GOME-2 SIF with two state-of-art GPP products (i.e. FLUXCOM GPP and GLASS GPP) and flux tower observed GPP, using 2009 summer drought in Northeast China and 2010 spring drought in Southwest China as study cases. We found that SIF was a quantifying indicator of GPP and successfully characterized the temporal dynamics and spatial extents of GPP anomalies during the drought events, as well as accurately estimating the drought-induced GPP losses. Moreover, SIF (R2 = 0.87) performed better than enhanced vegetation index (R2 = 0.78) in capturing the photosynthesis changes induced by droughts, suggesting SIF was more sensitive to plant physiological changes. The strong positive correlations of SIF with Palmer drought severity index (PDSI) and root-zone soil moisture, further gave confidences on the capacity of SIF in vegetation drought monitoring. SIF had a time lag response to both PDSI and soil moisture, which might be attributable to the plants adaptation mechanisms for the drought occurrence and physiological recovery after water stress. Our study demonstrates that satellite-based SIF can achieve real-time vegetation drought monitoring and the assessment of drought-induced GPP anomalies at large scales, thus providing a unique opportunity to study the impacts of drought on vegetation carbon uptake.